2013
DOI: 10.7175/rhc.v4i3s.878
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic changes in pregnancy

Abstract: Normal pregnancy is associated with changes in all aspects of haemostasis, including increase in concentrations of most clotting factors, decreasing concentrations of some of the natural anticoagulants and diminishing fibrinolytic activity. These changes help in maintaining placental function during pregnancy but result in a state of hypercoagulability that may predispose to thrombosis and placental vascular complications. During pregnancy, the concentrations of coagulation factors V, VII, VIII, IX, X, XII and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…In this study, significantly lower and fluctuations of platelet counts have been observed during pregnancy compared to the puerperium. These findings are in agreement with earlier reports [5,[11][12][13]. Thrombocytopaenia has been associated with haemodilution and accelerated platelet consumption during pregnancy [13][14][15] while increased platelet count during puerperium could be associated with consumption of platelets and blood coagulation factors during delivery [6].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, significantly lower and fluctuations of platelet counts have been observed during pregnancy compared to the puerperium. These findings are in agreement with earlier reports [5,[11][12][13]. Thrombocytopaenia has been associated with haemodilution and accelerated platelet consumption during pregnancy [13][14][15] while increased platelet count during puerperium could be associated with consumption of platelets and blood coagulation factors during delivery [6].…”
Section: Discussionsupporting
confidence: 93%
“…There was significant difference in the levels of APTT when compared among the trimesters. This also agrees with the study of [17,18] who followed the same pattern. This might be due to increased synthesis or increased activation by coagulation factors.…”
Section: It Is Also Consistent With the Work Done By Hellgren In 2003supporting
confidence: 92%
“…Both plasma volume (+40%) and red blood cell volume (+25%) increase, leading to a state of haemodilution; as a result, approximately one‐third of pregnant women are anaemic at term 11 . Due to dilution and consumption by the uteroplacental unit, platelet count decreases during pregnancy from the first trimester, with the greatest reduction occurring during the third trimester 8 ; however, it increases immediately after delivery, especially in cases of caesarean delivery 11 …”
Section: Coagulation Profile Of Women With Pphmentioning
confidence: 99%
“…There are many haemostatic changes in normal pregnancy, including an increase in procoagulant factors (V, VII, VIII, IX, X, XII and von Willebrand factors), a decrease in some of natural anticoagulants (reduced protein S activity and acquired activated protein C resistance) and a decrease in fibrinolytic activity. These changes occur to support placental function but may lead to a state of hypercoagulability, resulting in an increased risk of thrombosis and placental vascular complications 11 …”
Section: Coagulation Profile Of Women With Pphmentioning
confidence: 99%